2013
DOI: 10.1177/0969141313497197
|View full text |Cite
|
Sign up to set email alerts
|

Use of a faecal immunochemical test narrows current gaps in uptake for sex, age and deprivation in a bowel cancer screening programme

Abstract: Objectives To investigate the characteristics of participants screened for bowel cancer using a faecal immunochemical test for haemoglobin (FIT). Setting Scottish Bowel Screening Programme. Methods 65909 men and women in two NHS Boards, aged 50 to 74, were invited to participate in an evaluation of FIT as a first-line test. Uptake was calculated by sex, age in quintiles, and deprivation in quintiles, and compared with a group who had completed a guaiac faecal occult blood test (gFOBT) and for whom details of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 22 publications
4
31
0
Order By: Relevance
“…The actual participation rates for each round are in keeping those reported previously for FIT [30,31]. Similarly, there were no significant changes in the sex or age profile of the respondents between the two rounds.…”
Section: Discussionmentioning
confidence: 85%
“…The actual participation rates for each round are in keeping those reported previously for FIT [30,31]. Similarly, there were no significant changes in the sex or age profile of the respondents between the two rounds.…”
Section: Discussionmentioning
confidence: 85%
“…Of these, the two largest studies, both in the Netherlands, which found uptake to increase from 46.9% or 49.5% with gFOBt to 59.6% or 61.5% with FIT, were both conducted in previously unscreened populations 13 15. A study in Scotland has reported overall uptake of 58.7% with FIT compared with 53.9% for gFOBt, with higher uptake in all age and deprivation quintiles for both men and women 18 19. However, in the Scottish study FIT uptake and clinical outcomes in two evaluation NHS boards were compared with results obtained contemporaneously in two other similar NHS boards and before and after the evaluation of FIT.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-notification letter was associated with a marked increase (from 53.9% to 59.0% -OR = 1.24) in the response to the invitation for gFOBT screening in the Scottish programme (Libby et al, 2011), with a similar trend by age, gender, SES and screening history. However, a recent report (Digby et al, 2013) from the same programme, showing that, maintaining the standard invitation procedure, a comparable increase in the participation (from 53.9% to 58.7%) could be achieved by offering FIT as compared to gFOBT, would suggest that the impact of a pre-notification letter might be lower when adopting a more acceptable strategy (single sample and simplified stool collection procedure).…”
Section: Discussionmentioning
confidence: 85%